1987
DOI: 10.1128/iai.55.2.335-341.1987
|View full text |Cite
|
Sign up to set email alerts
|

Induction of murine gamma interferon production by lipopolysaccharide and interleukin-2 in Propionibacterium acnes-induced peritoneal exudate cells

Abstract: Lipopolysaccharide (LPS) induces high levels of gamma interferon (IFN-,y) in the circulation of mice pretreated with heat-killed Propionibacterium acnes. The following results were obtained in the present study. (i) LPS, as well as interleukin-2 (IL-2), was also able to induce IFN-y in vitro in peritoneal exudate cells (PEC) from such mice. Splenocytes and lymph node cells from these mice or resident peritoneal cells from control mice produced trace or undetectable amount of IFN-y upon exposure to LPS. (ii) A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

1989
1989
2000
2000

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…Regarding IFN-g our results showing high levels of production in INMD-stimulated cells indicated that combination of Propionibacterium and LPS in pigs produced a higher induction potential than any compounds alone over NK or other IFN-g-producing cells in pigs. This has been observed before by other authors in humans and mice (Hirt et al, 1978;Okamura et al, 1982;Kirchner et al, 1986;Okamura et al, 1987).…”
Section: Discussionsupporting
confidence: 84%
“…Regarding IFN-g our results showing high levels of production in INMD-stimulated cells indicated that combination of Propionibacterium and LPS in pigs produced a higher induction potential than any compounds alone over NK or other IFN-g-producing cells in pigs. This has been observed before by other authors in humans and mice (Hirt et al, 1978;Okamura et al, 1982;Kirchner et al, 1986;Okamura et al, 1987).…”
Section: Discussionsupporting
confidence: 84%
“…Lipopolysaccharides (LPS) of Gram-negative bacteria are potent stimulants of many cytokines, such as IL-1, IL-6 and INF-a [1,5,10,11]. Until recently, few studies of cytokine stimulating activity of different Gram-positive bacteria and their cell surface components and extracellular products have been available [1,8,11,12,16,17]. However, it is known that some of the symptoms in septic shock, caused by S. aureus, may be associated with overproduction of IL-1 and TNF-a stimulated by toxic shock syndrome toxin-1 (TSST-1) [1,5,12].…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted, however, that because of the complex, regulatory functions of IFN-7, contribution of this lymphokine to the pathogenesis of other infections is also important. IFN-y enhances different functions of macrophages and stimulates the antibody secretion of B cells [1,5,16,22,29]. IFN-T also increases in vitro production of TNF-a by cultured macrophages and probably augments synthesis and their biological activity in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…It has recently been reported that mice injected with heat-killed Propionibacterium acnes released significantly higher levels of interferon-␥ (IFN-␥) into the circulation on challenge with T cell mitogens than mice challenged with T cell mitogens alone [1][2][3][4]. This IFN-␥ production was also induced in vivo when using lipopolysaccharide (LPS) as a mitogen instead of T cell mitogens [5][6][7].…”
Section: Introductionmentioning
confidence: 99%